2014
DOI: 10.1080/00423114.2014.982136
|View full text |Cite
|
Sign up to set email alerts
|

<TPL-PCRUN> Statement of methods

Abstract: TPL-PCRUN is a software program for the dynamic interaction simulation of pantograph-catenary systems. In the benchmark, based on the finite element method, the catenary model was built and the pantograph was considered as a three-level spring-damper-mass system. Then, through the contact definition between pantograph and catenary, the coupled model of the pantograph and catenary system was established. The respective dynamic equations of motions were solved by the time integration method. Thus, the simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…This is due to the unilateral non-linearity exhibited by the droppers, which tend to slacken and make the catenary more flexible. Comparing the optimal catenary configurations with respect to their reference configura- (13) This coefficient is calculated for all the eight catenaries, as shown in Table 7. A large decrease of the stiffness variability is noticed in the optimal Benchmark catenaries if compared with the reference configuration.…”
Section: Static Characteristics Of the Optimal Catenariesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the unilateral non-linearity exhibited by the droppers, which tend to slacken and make the catenary more flexible. Comparing the optimal catenary configurations with respect to their reference configura- (13) This coefficient is calculated for all the eight catenaries, as shown in Table 7. A large decrease of the stiffness variability is noticed in the optimal Benchmark catenaries if compared with the reference configuration.…”
Section: Static Characteristics Of the Optimal Catenariesmentioning
confidence: 99%
“…This explains why in recent years a lot of effort has been put into developing accurate models capable of simulating the dynamic pantograph-catenary interaction. Among the vast diversity of studies found in the literature, [3][4][5][6][7][8][9][10][11][12][13] deserve special mention as they participated in a benchmark [14], and give a good insight into the present state of the art.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, effort has been made to minimize such fluctuations through optimization of the elements used in the pantograph or catenary system. A multitude of software programs written in this field in recent years reflects the importance of the issue [2][3][4][5][6][7][8][9][10][11]. In addition, part of the researches are concentrated with controlling the pantograph through the estimation of the level of force via various methods and prevent any significant changes by applying controlling forces [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Other iterative methods, such as the negative-sag method applied in [34] or the one used in [21,33], are based on linear formulations and proceed by modifying the dropper lengths at each step of the procedure. Analytic expressions for calculating length of droppers and pre-sag of messenger wire are also found in [43].…”
Section: Initial Configuration Problemmentioning
confidence: 99%
“…Although some authors do not allow for dropper slackening [24][25][26][27][28][29][30], it is an important feature that should be regarded in the models as stated in [31], where experimental curves of dropper behaviour are provided. Due to the low bending stiffness of these elements, most dropper models are based on either a mass-spring-damper system with slackening [20,[32][33][34] or a bar element with slackening [22,[35][36][37][38]. These two options are also used to model steady arms [31].…”
Section: Catenary Modellingmentioning
confidence: 99%